Bioassays of Humoral Cardioprotective Factors Released by Remote Ischemic Conditioning in Patients Undergoing Coronary Artery Bypass Surgery. (5th May 2022) - Lieder, Helmut Raphael; Tüller, Pia; Braczko, Felix; Zandi, Afsaneh; Kamler, Markus; Thielmann, Matthias; Heusch, Gerd; Kleinbongard, Petra
Remote ischemic conditioning (RIC) induces the release of circulating cardioprotective factors and attenuates myocardial ischemia/reperfusion injury. Evidence for such humoral cardioprotective factor(s) is derived from transfer with plasma (derivatives) from one individual undergoing RIC to another individual's heart, even across species. With transfer into an isolated perfused heart, only a single plasma (derivative) sample can be studied with infarct size as endpoint, and therefore the comparison of samples before and after RIC or between RIC and placebo is hampered by the inter-individual variation of infarct sizes in isolated perfused hearts. We therefore developed a preparation of cardiomyocytes from a single mouse heart, where aliquots of the same heart can undergo hypoxia/reoxygenation (H/R) with exposure to buffer, RIC, or placebo samples without or with pharmacological blockade. To validate this approach, we used plasma dialysates taken before and after RIC from patients undergoing coronary bypass grafting who had experienced protection by RIC (troponin release ↓ by 28% vs placebo). The cardiomyocyte bioassay had little variation after H/R with buffer (mean ± standard deviation; 7% ± 2% viable cells) and demonstrated preserved viability after RIC (15% ± 5% vs 6% ± 3% before). For comparison, infarct size in isolated mouse hearts after global ischemia and reperfusion was 22% ± 14% of left ventricular mass after versus 42% ± 14% before RIC. Stattic, an inhibitor of signal transducer and activator of transcription (STAT)3 protein, abrogated protection in the cardiomyocytes. We have thus established a cardiomyocyte bioassay to analyze RIC's protection which minimizes inter-individual variation and the use of animals.